Magnetic method applying for the control of productive land degradation - O. I. Menshov (Геофизический журнал, 2016)
The development of agriculture in Ukraine requires increasing of the crop yields, which can lead to soil and humus loss, soil erosion and land degradation. The task of soil mapping and modeling within the farm lands is important to predict and control hazard processes in soil. The expected result is the elaboration of the optimal schemes of land exploitation and sustainable use management. To solve these tasks we propose to involve magnetic methods of the soil studies. They give us highly informative techniques based on our own and international experience. The first case of our investigation is magnetic susceptibility of agricultural land within Kharkiv region. The soil is presented by chernozems. We registered the average value of the soil mass-specific magnetic susceptibility (χ): 69×10–8 m3/kg; minimum value is 50×10–8 m3/kg; maximum value is 86×10–8 m3/kg. The coefficient of variation is 12.48 %, which indicates the low variability of magnetic susceptibility within the area. This indicate the absence of the soil type change and technogenic impact.  The second example was conducted within the Odessa region. The landscape represents the plain with the bluff near the sea lanes. Lateral cross-section was investigated to identify the parts with the high level of soil erosion dangerous. The magnetic susceptibility of highly magnetic not disturbed southern chernozems reached 160×10–8 m3/kg. We identified the points of the replacement of top soil. This eroded soil, which was presented by underlying clay horizon, has the magnetic susceptibility about 80×10–8 m3/kg. Humus content in soil is closely connected with the formation of magnetic minerals in the soil under the pedogenic process. We mean in this case the absence of the anthropogenic and technogenic impact. The formation of magnetic minerals is controlled only by the presence of organic matter in soil aggregates and favorable conditions for the iron valence change. The productive Ukraine top soil contains fine-grained oxidized magnetite and maghemite of pedogenic origin formed by weathering of the parent material. This soil is often presented by chernozems from the farm lands with the high level of erosion risk. The formation of the magnetite is related to the magnetotactic bacteria functions.